Analysis of haloacetic acids in water and air (aerosols) from indoor swimming pools using HS-SPME/GC/ECD - Sá, Christopher S.A. (2017)
A solid phase microextraction method was used for the analysis of nine haloacetic acids (HAAs) in water and air (aerosols) from indoor swimming pools (ISPs). The analysis is characterized by derivatization of HAAs to their methyl-esters with dimethyl sulphate, headspace solid phase microextraction (HS-SPME) with a Carboxen–polydimethylsiloxane (CAR-PDMS) fiber and gas chromatography - electron capture detector (GC/ECD). High correlation coefficients were obtained for esters mixture calibration lines and detection limits were found to be at the low ppb level. Repeatability was assessed and coefficients of variation varied from 10 to 20%. Reproducibility was also evaluated and coefficients of variation from 15 to 25% were obtained. Analytical results from four Portuguese ISPs showed that the mean concentration of total HAAs (THAAs) in water ranged from 10 ± 2 to 183 ± 28 μg/L in which 55 ± 20% corresponded to trichloroacetic and dichloroacetic acids (TCAA and DCAA). THAAs highest concentrations were directly related to higher ISPs’ water organic matter content. In the lack of European specific regulation for water from ISPs and taking into consideration that ingestion is a form of exposure, THAAs concentration values were compared with drinking water maximum contamination level (MCL) of 60 μg/L proposed by the US EPA for the sum of five HAAs. In 35% of water sampling campaigns the sum of MBAA (monobromoacetic acid), MCAA (monochloroacetic acid), DCAA and TCAA exceeded that MCL value. The concentrations obtained for THAAs in the ISPs’ atmosphere ranged from 5 ± 1 to 64 ± 10 μg/m3 (T = 28◦C at 5 cm above the water surface) and were proportional to the aerosols’ quantity, which was deeply related to indoor air ventilation system.